The pioneers : the heroic story of the settlers who brought the American ideal west - McCullough, David G (Simon & Schuster, 2019)
"Best-selling author David McCullough tells the story of the settlers who began America's migration west, overcoming almost-unimaginable hardships to build in the Ohio wilderness a town and a government that incorporated America's highest ideals"--